The world of ornament complete coloured reprint of L'Ornement polychrome (1869-1888) & L'Ornement des tissus (1877) - Racinet, A. (Auguste) 1825-1893 Ornement polychrome; Dupont-Auberville, A. Ornement des tissus (Bibliotheca universalis, 2015)
"The World of Ornament brings together the two greatest encyclopedic collections of ornament of the 19th century: Auguste Racinet's L'Ornement polychrome Volumes I and II (1875-1888) and M. Dupont-Auberville's L'Ornement des tissus (1877) to provide one lavish source book spanning jewelry, tile, stained glass, illuminated manuscript, textile and ceramic ornament." -- Provided by publisher